Organic residues in Eisenia poetida L reproduction and as lombricompost - Gilces Reyna, Maria Amparo (2024)
The objective of this study was to evaluate the effect of residues on the reproduction of E. foetida, the physicochemical characteristics and phytotoxicity of vermicompost. In this research, 8 treatments were analyzed: T1: bovine manure, T2: poultry manure, T3 corn chaff, T4: peanut shell, T5: bovine manure + corn husk, T6: bovine manure + peanut shell, T7: poultry manure + corn chaff and T8: poultry manure + peanut shell. Reproduction parameters such as number, size and weight of worms were evaluated. The physicochemical parameters of the vermicompost analyzed were yield, moisture, bulk density, pH, electrical conductivity, nitrogen, phosphorus and potassium concentration, while phytotoxicity was analyzed against Lactuca sativa seeds. The results obtained showed that T1 was able to reproduce 912 units with an average length of 4,86 cm and generated 17,17 kg of vermicompost, T7 presented a higher concentration ofnitrogen (2,64%) and organic matter content of 52,71%, the pH remained in neutral values (6,9-7,2), while the electrical conductivity was low (0,22-0,64 ds/m). None of the treatments showed toxicity to L. sativa seeds, but T1, T3, T4, T5, T7 and T8 showed phytostimulant activity on seed germination. Biological transformation of wastes is an important tool for waste management that influences E. foetida reproduction, yield, vermicompost quality and stimulates L. sativa germination.